2001
DOI: 10.1063/1.1400771
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and lateral GaN rectifiers on free-standing GaN substrates

Abstract: Edge-terminated Schottky rectifiers fabricated on quasibulk GaN substrates showed a strong dependence of reverse breakdown voltage VB on contact dimension and on rectifier geometry (lateral versus vertical). For small diameter (75 μm) Schottky contacts, VB measured in the vertical geometry was ∼700 V, with an on-state resistance (RON) of 3 mΩ cm2, producing a figure-of-merit VB2/RON of 162.8 MW cm−2. Measured in the lateral geometry, these same rectifiers had VB of ∼250 V, RON of 1.7 mΩ cm2 and figure-of-merit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…The knee voltage (V k ) of the proposed L-FER is 0.2 V, where V k is defined as the anode bias at a forward current of 1 mA/mm. This V k is much lower than those reported in SBDs and p-i-n rectifiers that are typically ~ 1 V [8][9][10][11][12][13][14][15][16]. Such a large difference is a result of the different turn-on mechanisms.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…The knee voltage (V k ) of the proposed L-FER is 0.2 V, where V k is defined as the anode bias at a forward current of 1 mA/mm. This V k is much lower than those reported in SBDs and p-i-n rectifiers that are typically ~ 1 V [8][9][10][11][12][13][14][15][16]. Such a large difference is a result of the different turn-on mechanisms.…”
contrasting
confidence: 45%
“…However, for the development of low-cost GaN-based integrated power converters that require both HEMT switches and rectifiers, it is desirable to integrate highperformance power transistors and rectifiers on the same epitaxial wafer with the same fabrication process. Up to now, the development of GaN-based discrete high voltage power transistors and rectifiers has been mainly developed on different epitaxial structures, hindering the monolithic integration of power transistors and rectifiers for power integrated circuits [8][9][10][11][12][13][14]. This is mainly due to the incompatibility between epitaxial structures of HEMT structure and diodes.…”
mentioning
confidence: 99%
“…42 It has previously been suggested that β is a strong function of the defect type and density present in the homoepitaxial GaN and that positive values might be obtained in true bulk material. 1,41 …”
Section: Resultsmentioning
confidence: 98%
“…There is still a need for more detailed understanding of the electrical properties of implanted p/n layers in GaN because of their potential application in simple electroluminescent displays or power rectifiers. 41 In this paper, we report on the creation of GaN Schottky diodes by Si ϩ ion implantation into p-GaN. The current-voltage (I-V) characteristics were measured as a function of annealing temperature along with the Si ϩ activation percentage.…”
Section: Introductionmentioning
confidence: 99%
“…The highest quality GaN epitaxial layers would ideally be achieved by homoepitaxy using a GaN substrate which is identical in crystal structure, lattice constant and thermal expansion coefficient. This homoepitaxy template can be achieved by means of a freestanding (FS-GaN) crystal, (obtained after the growth and separation of several hundred micrometers of GaN on a foreign substrate), but such FS-GaN layers still contains several types of imperfections such as scratches and/or edge pits [10][11][12][13][14][15][16][17]. The inherent FS-GaN defects extend into the HEMT active layers and may degrade the charge transport mechanisms, particularly increasing the HEMT off-state leakage currents which, in turn, reduces the breakdown voltage.…”
mentioning
confidence: 99%